Biosimilar: Understanding the Concepts and Developing role in Nephrology. (Pakistan Journal of Kidney Diseases, 2021)
Biosimilars are designed to be used interchangeably with biologics and its development is an attempt to reduce the cost of health care. Biologics have variety of uses and are created in living cells. They are typical large complex proteins which can be used in different medical conditions. Biosimilars are a growing drug class and must be nearly identical to their reference biologics in terms of efficacy, side effect profiles and immunogenicity. The low cost of biosimilar is likely to be because it underwent fewer clinical trials. The manufacturing process still involved production in living cells. Erythropoietin biosimilar product is widely used in nephrology practice since 2013. Biosimilars are facing challenges in establishing a significant market share despite of their low cost. This seems to be a reflection of physicians being not confident in switching and patients as well show resistant to switch.Long term safety and efficacy data is required in addition to increase number of available biosimilar products to improve the confidence of physician and patient. Biosimilar products will require more time to leave significant impact on the market share.
Keywords: NEMI; biosimilR; erythro[oietin; chronic kidney disease.